The Crisis of the Agency for Customary Institutions (Keujruen Blang): From the New Order, Reformation to Peace of Aceh - Mursyidin, Mursyidin; Saputra, Akmal; Baihaqi, Baihaqi; Saputra, Jumadil; Siregar, Wardah Muharriyanti (SCAD Independent, 2023)
This article examines why the Keujruen Blang, as a traditional institution, has continued to experience crises since the New Order Reformation to post-peace in Aceh. This study aimed to reveal and provide an overview of how the Acehnese people's local wisdom, or local knowledge, has been experiencing a crisis, particularly a recent issue with paddy field management. This study was conducted in Aceh Jaya and used qualitative research. Observations and direct interviews were conducted with 17 informants. The technique for determining informants used a purposive technique. In addition to the interview, data were collected through a review of the literature and other documents on the crisis agency of local actors (keujruen blang). These related documents and articles were identified, reviewed, and analyzed. The data analysis techniques used was data reduction, data display, and verification. Reproduction of the keujruen blang authority had yet to bring the expected results. Even though laws, government regulations, and Aceh Qanun had been issued, Keujruen Blang still needed to be strengthened. This fact occurred because there were overlapping roles and functions between the customary institution of keujruen blang and the formal P3A institution.